2011
DOI: 10.3354/meps09261
|View full text |Cite
|
Sign up to set email alerts
|

Aerial survey abundance estimates of the loggerhead sea turtle Caretta caretta in the Pelagos Sanctuary, northwestern Mediterranean Sea

Abstract: Aerial line transect surveys, totalling 16 590 km, were performed in winter and summer 2009 in the Pelagos Sanctuary, NW Mediterranean. A total of 207 loggerhead sea turtles were sighted, with only 9 sightings during the winter. In this season average raw 'surface' density (i.e. animals at or near the surface) was 0.002 turtles km -2 , and on the basis of line-transect analysis, we estimated 237 specimens (CV = 34.33%; 95% CI = 122-461). The summer estimate resulted in 4083 animals at surface (CV = 14.59%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…In some areas, like the western Mediterranean (Revelles et al 2007b) and the Tunisian shelf (Casale et al 2012b), no seasonal movement patterns were observed through satellite tracking. In contrast, individuals foraging in the north Adriatic have been found to move southwards in winter, as observed also in adults (see above), and in the Ligurian Sea (Lauriano et al 2011). For instance, Casale et al (2012a) tracked one individual during a complete migration cycle, with an autumn southwards migration along the Italian coast in the western Adriatic and a northwards spring return to the very same site following a route along the eastern Adriatic coast (Figure 2).…”
Section: Large Juvenilesmentioning
confidence: 89%
See 2 more Smart Citations
“…In some areas, like the western Mediterranean (Revelles et al 2007b) and the Tunisian shelf (Casale et al 2012b), no seasonal movement patterns were observed through satellite tracking. In contrast, individuals foraging in the north Adriatic have been found to move southwards in winter, as observed also in adults (see above), and in the Ligurian Sea (Lauriano et al 2011). For instance, Casale et al (2012a) tracked one individual during a complete migration cycle, with an autumn southwards migration along the Italian coast in the western Adriatic and a northwards spring return to the very same site following a route along the eastern Adriatic coast (Figure 2).…”
Section: Large Juvenilesmentioning
confidence: 89%
“…Finally, other sources of information can provide clues on turtle distribution, such as stranding data (Tomás et al 2008;Türkozan et al 2013), incidental catch in fishing gears (reviewed by Casale 2011) and aerial surveys (Gomez de Segura et al 2006;Lauriano et al 2011). …”
Section: Methods For Studying Sea Turtle Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a lower stranding turtle density (which, however, may be affected by several factors, including currents) was observed in the north (0.05 turtles km ) (Deflorio et al 2005, Cambiè et al 2010. Finally, aerial surveys indicate a lower turtle density during summer in the north Tyrrhenian (0.046 turtles km −2 ) (Lauriano et al 2011) than in the westernmost part of the basin (0.21 turtles km −2 ) (Gomez de Segura et al 2006), mainly frequented by loggerhead turtles from the Atlantic (Carreras et al 2006). Moreover, observations of the surface currents using Lagrangian drifters (Poulain & Zambianchi 2007) show that a persistent southeastward circulation is present in the Sicily Channel throughout the year.…”
Section: Comparison With Empirical Data On the Distribution Of Older mentioning
confidence: 99%
“…Bentivegna et al 2007, Broderick et al 2007, Revelles et al 2007b, Schofield et al 2013, genetic markers (e.g. Carreras et al 2006, Garofalo et al 2013, and aerial surveys (Gomez de Segura et al 2006, Lauriano et al 2011. However, most observations relate to the western and central Mediterranean, while less information is available for the easternmost part (the Levantine basin).…”
mentioning
confidence: 99%